2017
DOI: 10.1021/acs.jpcb.6b12450
|View full text |Cite|
|
Sign up to set email alerts
|

Deficiencies in Molecular Dynamics Simulation-Based Prediction of Protein–DNA Binding Free Energy Landscapes

Abstract: Transcriptional regulation allows cells to match their gene expression profiles to their current requirements based on environment, cellular physiological state, and extracellular signals. DNA binding transcription factors are major agents of transcriptional regulation, and bind to DNA with a factor-specific sequence preference to exert regulatory effects. A crucial step in unraveling the logic of a regulatory network is determining the sequence-specific binding affinity landscapes for the transcription factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 37 publications
1
44
0
Order By: Relevance
“…Several approaches were developed to accurately and precisely reveal the nature of binding between a compound to a protein, a protein to a protein, and a protein to a gene, etc., [1][2][3][4] because the non-covalent reaction between two biomolecules is very important in biology. [5][6][7][8] Especially, the ligand-binding affinity is one of the most critical aspects to predict a potential inhibitor restricting the biological function of an enzyme in computer-aided drug design (CADD).…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches were developed to accurately and precisely reveal the nature of binding between a compound to a protein, a protein to a protein, and a protein to a gene, etc., [1][2][3][4] because the non-covalent reaction between two biomolecules is very important in biology. [5][6][7][8] Especially, the ligand-binding affinity is one of the most critical aspects to predict a potential inhibitor restricting the biological function of an enzyme in computer-aided drug design (CADD).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, high-resolution determinations of protein–DNA complex structures ( 18 ) allow one to investigate corresponding conformational dynamics by employing all-atom molecular-dynamics (MD) simulations via high-performance computing ( 19 21 ). Protein recognition on specific DNA has been actively examined in recent years using MD technologies ( 22 26 ). In comparison, protein association with nonspecific DNA has been less examined.…”
mentioning
confidence: 99%
“…A computational study by Khabiri et al, 2017 reported that changes in binding free energy do not correlate strongly with salt bridges or hydrogen bonding in protein-DNA interactions [ 43]. Contrary to their results, we show that for our peptide-DNA systems the electrostatic energy and binding free energy are correlated with the number of hydrogen bonds and salt bridges ( Figure 10), with an R 2 between binding free energy and the number of hydrogen bonds and salt bridges of -0.92 and -0.95, respectively, and an R 2 of -0.95 and -0.97 between electrostatic energy and hydrogen bonds and salt bridges, respectively.…”
Section: Contacting Surface Areamentioning
confidence: 99%